Role of politics in public sector organizational change - Sepper, Ruth; Alas, Ruth (Journal of Business Economics and Management, 2008)
In this paper we will address issues of organizational changes in public sector where the relevance of management has not diminished during the last two decades of the neo‐liberal market philosophy. Public sector organizations are susceptible to greater and more open accountability with politicians, pressure groups, taxpayers and voters all having an interest in the performance of it. In late 1990s Estonian government initiated reforms of health care system in the country. Estonian Hospital Master Plan (EHMP) 2015 was launched in 2000 which, within the others, was initiating the merge of seven Tallinn hospitals into North Estonian Regional Hospital (NERH). To evaluate efficacy of organizational changes during implementation of EHMP‐model into health care system in Estonia we utilized personal interviews of top and middle managers and annual reports of merged hospitals to benchmark these measures to earlier merged Univerity Hopsital and other EU hospitals. We conclude that even NERH was established and the reform‐initiated changes were mostly introduced by the deviation from first‐line governmental plans and introduction of new political directions in 2003 lead to new organizational changes and managerial efforts to gain the goals with, unfortunately, prolonged change process.First published online: 14 Oct 2010